Features of civil liability of police officers for damage caused under the influence of force majeure - Lilia, Strelbytska; Mykola, Strelbytskyi; Viktor, Shemchuk; Mykhailo, Rizak; Khrystyna, Kulhavets (Cuestiones Políticas, 2020)
The aim of the article is to analyze the characteristics of civil liability of Ukrainian police officers for damage caused under the influence of force majeure. At a methodological level to achieve the objectives of the article, the following scientific methods were combined: general (dialectical, formal-logical, system-structural) and special (historical, comparative-legal, etc.). Essentially, the concept of force majeure and its characteristics are studied, as well as two main theories of force majeure (objective and subjective). In addition, the main differences between force majeure and case are established. The types of force majeure circumstances and their particular properties are studied. By way of conclusion, the fact that police officers are exonerated from civil liability for causing damage under the influence of force majeure is discussed, if they can prove the effect of this influence. For the rest, given that Ukraine's jurisprudence on the exemption from civil liability of police officers due to force majeure is quite limited to formulating a precedent, it is based on the general rule that, in tort, the recognition that the damage was the result of accidental circumstances excludes the occurrence of liability for damages.